Analysis of ANC Levels after Filgrastim Therapy in Acute Leukemia Children with Neutropenia - Widya, Reta Anggraeni; Nugroho, Susanto; Winarsih, Sri; Yulistiani, Yulistiani (Folia Medica Indonesiana, 2019)
Cytotoxic chemotherapy suppresses the hematopoietic system, and the most serious hematologic toxicity is neutropenia. This can decrease a risk of infection that causes delays in treatment and reduction of dose intensity, which reduces therapeutic outcome. Filgrastim is used to increase neutrophils level whose therapeutic effect is unknown. The effectiveness of filgrastim is based on the ANC level pre- and post-therapy. This study aimed to analyze the use of filgrastim on ANC level changes in acute leukemia children with neutropenia, and to analyze the patient that achieve ANC level's targeted therapy = 1000 cell/mm3. A prospective observational study with a longitudinal design was conducted from June to October 2016. The inclusion criteria of the study were patients who diagnosed acute leukemia with neutropenia and received filgrastim 10 µg/kgBW for 3, 4, 5 days. Patients' ANC levels were measured before and after filgrastim therapy. This study has been approved its ethical clearance by Dr. Saiful Anwar Hospital, Malang. Data were obtained on the basis of neutropenic episodes, followed by 7 episodes of obtaining filgrastim for 3 days, 1 episode of obtaining filgrastim for 4 days, and 7 episodes of obtaining filgrastim for 5 days. Thus, it consists of 15 episodes. In 3 days, ANC levels increased by 9.5 fold from 381.3 ± 91.8 cell/mm3 to 3984.9 ± 426.8 cell/mm3, but in 5 days, ANC levels decreased by 0.9 fold from 200.9 cell/mm3 ± 98.2 to 189.7 ± 14.2 cell/mm3. Filgrastim was able to increased the ANC levels around nine fold for 3 days of theraphy. There were 53% neutropenia patients who achieved the goal of therapy. Filgrastim therapy with dose 10 µg/kgBW for 3 to 5 days has been able to reach the therapeutic target of 53% in acute leukemia children with neutropenia. The increased levels of ANC maximum was reached on the third day with increased levels of 9.5 fold.